Tinjauan Yuridis Tata Ruang dan Lingkungan pada Proyek Reklamasi PIK 2 Berdasarkan PP 21 dan Pp 22/2021 - Farida Nurun Nazah; Naya Indah Sahqia; Alisya Putri Santoso; Nova Reana Wahida; Suryajaya Hakim; Asyifa Nayla Jingga (Jurnal Hukum Lex Generalis, 2026)
The coastal reclamation project in the Pantai Indah Kapuk 2 (PIK 2) area has attracted attention from an environmental law perspective due to its potential implications for the alignment of coastal development, spatial planning and environmental protection. This study aims to analyze the conformity of the PIK 2 reclamation project with environmental damage prevention and control instruments as regulated under Government Regulation Number 22 of 2021, as well as its relationship with the principle of spatial planning conformity stipulated in Government Regulation Number 21 of 2021. This research employs a normative juridical method using statutory, conceptual and analytical approaches through the examination of laws and regulations, legal literature and other relevant documents. The findings indicate the presence of potential inconsistencies in the implementation of the Environmental Impact Assessment (AMDAL) and the assessment of Environmental Carrying Capacity (DDLH), as well as possible misalignments between environmental protection objectives and the utilization of coastal areas. Furthermore, environmental monitoring and enforcement mechanisms continue to face various challenges that require further verification and assessment to determine their effectiveness in supporting environmental protection. The study highlights the importance of strengthening the integration of spatial planning and environmental management instruments, enhancing transparency in environmental governance and optimizing monitoring mechanisms to support sustainable and ecologically just coastal management.